GsMTx-4 venom toxin antagonizes biophysical modulation of metastatic traits in human osteosarcoma cells - Arianna Buglione; Giulia Alloisio; Chiara Ciaccio; David Becerril Rodriguez; Simone Dogali; Marco Luce; Stefano Marini; Antonio Cricenti; Magda Gioia (European Journal of Cell Biology)
Despite their genetic diversity, metastatic cells converge on similar physical constraints during tumor progression. At the nanoscale, these forces can induce substantial molecular deformations, altering the structure and behavior of cancer cells. To address the challenges of osteosarcoma (OS), a highly aggressive cancer, we explored the mechanobiology of OS cells, in vitro. Using uniaxial-stretching technology, we examined the biophysical modulation of metastatic traits in SAOS-2, U-2 OS, and non-tumorigenic hFOB cells. Changes in cell morphology were quantified using confocal and fluorescence microscopy. To elucidate the molecular mechanisms that translate biomechanical alterations into biochemical responses, we employed Western blotting, real-time quantitative RT-PCR, reactive oxygen species ROS assay, and the mechanosensitive channel blocker Grammostola MechanoToxin4 (GsMTx-4). Our study reveals that mechanical stimulation uniquely affects OS cells, increasing nuclear size and altering the N/C ratio. We found that mechanosensitive (MS) channels are activated, leading to ROS accumulation, Src protein modulation, and histone H3 acetylation. These changes influence OS cell motility and adhesion but not proliferation. Importantly, mechanical preconditioning differentially impacts doxorubicin resistance, correlating with the Src-H3 acetylation axis. This study underscores the critical role of MS channels in OS cells and highlights the importance of mechanobiology in identifying molecular pathways that traditional biochemical approaches may not reveal. Notably, the GsMTx-4 venom peptide effectively countered mechanically induced responses, particularly by inhibiting OS cell migration, without harming healthy cells. Thus, suggesting its potential as a promising therapeutic agent for targeting osteosarcoma metastasis